Chronic pain has a strong impact on quality of life in facioscapulohumeral muscular dystrophy. Issue 3 (7th November 2017) - Morís, Germán; Wood, Libby; FernáNdez‐Torrón, Roberto; González Coraspe, José Andrés; Turner, Chris; Hilton‐Jones, David; Norwood, Fiona; Willis, Tracey; Parton, Matt; Rogers, Mark; Hammans, Simon; Roberts, Mark; et al.
ABSTRACT: Introduction: Earlier small case series and clinical observations reported on chronic pain playing an important role in facioscapulohumeral dystrophy (FSHD). The aim of this study was to determine the characteristics and impact of pain on quality of life (QoL) in patients with FSHD. Methods: We analyzed patient reported outcome measures collected through the U.K. FSHD Patient Registry. Results: Of 398 patients, 88.6% reported pain at the time of study. The most frequent locations were shoulders and lower back. A total of 203 participants reported chronic pain, 30.4% of them as severe. The overall disease impact on QoL was significantly higher in patients with early onset and long disease duration. Chronic pain had a negative impact on all Individualised Neuromuscular Quality of Life Questionnaire domains and overall disease score. Discussion: Our study shows that pain in FSHD type 1 (FSHD1) is frequent and strongly impacts on QoL, similar to other chronic, painful disorders. Management of pain should be considered when treating FSHD1 patients. Muscle Nerve 57 : 380–387, 2018